Analisis Organologi Kacapi Semi Elektrik Karya Unen Supardi di Sanggar Aldi Kacapi - Aldi Nurhidayat Iskandar (Journal Social and Humaniora, 2024)
This research aims to provide knowledge to the public about how to choose a good and correct semi-electric harp. A harp that can be said to be of good quality can be seen from several aspects such as the sound it produces, the quality of the raw materials, and the aesthetics of the shape of the harp. The research method used in this research is descriptive analysis with a qualitative approach. The object of this research is the semi-electric lute by Unen Supardi. Data collection techniques in this research used observation, interviews, documentation and literature study. The research results obtained are that in producing a quality harp, you must really be able to take into account and understand the quality of the materials, the manufacturing process, the application of organological science with an aesthetic touch without reducing the quality of the sound itself.